PENYEMBUHAN PENYAKIT: SEBUAH STUDI EKSEGETIS BERDASARKAN MARKUS 16:17-18 - Made Nopen Supriadi (Manna Rafflesia, 2018)
The Lord Jesus before ascending to Heaven did say there would be signs accompanying believers, one of which was that they laid their hands on the sick, and the person was healed. Some groups really claim that every believer can cure a disease, is that right? To answer this question, it is very necessary to discuss Mark 16: 17-18. In this discussion using the Historical Redemptive method (redemptive history). So that through discussion with the History of the Atonement method you can understand the meaning of the text in the context of the History of the Atonement.